Depression, Anxiety and Stress of COVID-19 among Bachelor students in Health Science Colleges of Kathmandu - Kharel, Indu; Shrestha, Prabin; Maharjan, Luna; Pandit, Ramananda; Malla-Pradhan, Rajeshwori; Paudel, Manisha (Morgan Journal of Interdisciplinary Research Studies, 2024)
Depression is a mood disorder which leads to persistent feelings of sadness and loss of interest whereas, anxiety is a feeling of unease. Stress is the feeling of being unable to cope with mental and emotional pressure. Coronavirus Disease 2019 is a highly contagious disease caused by severe acute respiratory syndrome coronavirus 2. This study aimed to determine depression, anxiety and stress of COVID-19 among graduating students of bachelor degree in public health colleges of Kathmandu valley. The institutional based descriptive cross-sectional study was carried out among 314 students of five Bachelor in Public Health colleges of Kathmandu valley under Purbanchal University through convenience sampling method. Data was collected by using DASS-21 items through self-administration technique. Data was analyzed with IBM SPSS 20 version. The study found that out of 314 respondents, 73.2% of the respondents were in the 20-25 years age group with 67% female. Out of them, 30% were infected by COVID-19 and around 10% were hospitalized due to infection. It revealed that the prevalence of depression, anxiety and stress among public health students were 45.5%, 60.7% and 29.6% respectively. There is significant association between depression, anxiety and stress with COVID-19 infected respondents, respondents hospitalized due to infection as well as to those respondents whose family members were infected by COVID-19. The prevalence of depression, anxiety and stress of COVID-19 among graduating public health students was relatively high and shows that mental health is affected by COVID-19 pandemic.